O uso de biodigestores em pequenas e médias propriedades rurais com ênfase na agregação de valor: um estudo de caso da região noroeste do Rio Grande do Sul - Barichello, Rodrigo (2010)
From the duration of the Kyoto Protocol, there has been a renewed interest in technology of bio-digesters. As they allow a reduction in the emission of greenhouse gases compared to other waste treatment methods, their deployment can permit the marketing of carbon credits, resulting in money. The present study aims to analyze the process of dissemination of this technology in Santa Rosa, situated in the northwestern of Rio Grande do Sul state, especially powered by private companies. The profile properties that have these installed equipment, in addition to an examination of possible difficulties encountered by land owners, towards the deployment and use of this technology, with the contribution of biodigesters, on the energy issue and mitigation of environmental pollution in these areas. Through a revision of the existing literature and application of questionnaires some information about the installation of bio-digesters were taken, noticing if they contribute as alternatives in order to add value to the breeding properties and as viable alternative to the solution of environmental problems involved in the process. This study revealed that 33.33% of installed equipment is disabled. The work also presents a case study of isolated electric power generation using biogas as a fuel in an internal combustion engine of Otto cycle, in conjunction with CDM project, installed in a midsize property of pig breeding. The generation plant consists of a stationary Otto cycle engine, adapted to operate with biogas, coupled to an electric generator nominal 30 kVA three-phase. Through the study of the economic and financial feasibility, it was concluded that the application for generating electricity is viable and the overall efficiency of the system is satisfactory. Through another point of view, it presents a second case study, on the insertion of a property in a project of clean development mechanism (CDM) in pig production.